Academic Leadership and Organization Commitment Among Faculty Members in Malaysia Public Universiries - Asaari, Muhammad Hasmi Abu Hassan; Desa, Nasina Mat (Universiti Sains Malaysia, 2017)
The purpose of this paper is to examine the relationship between academic leadership and organizational commitment. The independent variable, academic leadership, is formed by visionary, adaptable to change, competency, effective leadership, transformational style and charisma while the dependent variable is organizational commitment. A total of 251 questionnaires were obtained from faculty members of public universities in Malaysia, which yielded a response rate of 41.8%. The results reveal that academic leadership, namely adaptable to change, transformational style and charisma, are significantly and positively related to organizational commitment. Comparison on mean values was done on gender, ethnic, highest education and universities on the factor of academic leadership. Theoretically, this paper contributes to the literature on academic leadership and organizational commitment. Practically, top management of public universities should consider trainings and courses on change, transformation and charisma that boost academic leadership of faculty members. In conclusion, this paper reveals the importance of change, transformation and charisma as factors of academic leadership in affecting organizational commitment of faculty members of public universities in Malaysia.